Attitudes of Implanting Physicians about Cardiac Rhythm Management Devices and Their Features. (26th December 2013) - Elmouchi, Darryl A.; Chalfoun, Nagib; Gauri, Andre
Abstract : Modern cardiac rhythm management systems have become increasingly complex. The decision on which specific system to implant in a given patient often rests with the implanting physician. We conducted a multiple-choice survey to assess the opinions and preferences of cardiologists and electrophysiologists who implant and follow cardiac rhythm management systems. Reliability and battery longevity were viewed as the most important characteristics in device selection. Patient characteristics which most affected device choice were pacing indication and life expectancy. Remote technology was used in 47% of pacemaker patients, 64% of ICD patients, and 65% of CRT-D patients, with wireless (radiofrequency) remote patient monitoring associated with higher patient compliance rates (74% versus 64%, resp.). Wireless remote patient management with alerts for atrial tachyarrhythmias was felt to be important by 76% of respondents. When choosing an MR-conditional device, physicians deemed patients with prior orthopedic problems, a history of cancer, or neurological disorders to be more likely to require a future MRI. Device longevity and reliability remain the most important factors which influence device selection. Wireless remote patient monitoring with alerts is considered increasingly important when choosing a specific cardiac rhythm management system to implant.